MENGUJI PENERAPAN ILMU TAJWID DALAM METODE IQRO: (Studi pada Pembacaan Al Quran di TPQ Al Ikhlas Klepu Sumber Manjing Wetan) - Hasib, Muhammad; Busyroel Basyar, Ahmad Beadie (JURNAL PUSAKA : Media Kajian dan Pemikiran Islam, 2021)
Reciting Al Quran is one of an essential medium for munajah to Allah SWT. For people to recite Al Quran correctly, they need to learn and practice it from expert teachers or ustadz or ustadzah. In learning to recite Al Quran correctly, the role of experts is practically significant. By its mean, this research is conducted with the purposes to study how ilmu tajwid in Iqro method commonly applied to the students. This research especially takes the students of TPQ Al Ikhlas in Klepu as the field research subject. Using qualitative descriptive, the data is classified into primary and secondary data. The results of this research shows that: the learning process of Ilmu ilmu tajwid in TPQ Al Ikhlas is helpful for students. Most of students, 67 of 72 pupils, are graduated from final evaluation. Secondly, the learning methods in the TPQ are distinguished by two categories, junior and senior grade. Junior grade teacher is intended to convey ilmu tajwid learning from basic, while the senior grade learn the mixing methods such as Iqro, Qiroati, and Tarsana. Senior grade also uses Syifaul Jinan, Qiroatul Huffadz, and Jazariyah as the learning resources.